O principal são as pessoas: uma abordagem comparativa das tecnologias da comunicação em Paulo Greire e Dominique Wolton - Caetano, Antoni Goncalves (2020)
From the theoretical reflection on the importance of the humanist dimension in the communication process, this work aims to identify and present possible discursive similarities between two thinkers on the subject, the Brazilian educator Paulo Freire and the French sociologist Dominique Wolton. Anchored in the bibliography of authors such as Manzini-Covre (2008), Martino (2017), Giddens (2002) and Lévy (1999) to contextualize the theme, this research also addresses topics such as citizenship, communication, social network, cyberspace and cyberculture. The analysis of these themes reinforces the thesis of the need to value the humanist dimension in the communication process. The text is divided into four chapters. In the first chapter we present a general concept of citizenship and its historical origin. Then, focusing on the right to communication for the exercise of citizenship, we describe some historical events under different interpretations and applications in the development of life in society. In the sequence, we approach communication, the organization of social networks and the changes undergone by technological advances that have significantly altered not only social organization, but life in society itself, giving rise to new concepts such as cyberspace and cyberculture. In the second chapter, we begin with a biographical synthesis about Freire. Then, focusing on the theme of this research, we analyzed three texts chosen by the author. For the third chapter, we also start by presenting a biographical summary of Wolton and then we also analyze three of his works. In the fourth and last chapter we analyze the possible discursive similarities identified between the authors regarding the importance of valuing the human dimension in the communicative process and present the common points found, as well as other points of view of different authors.